Meningkatkan Kinerja Guru dari Faktor Disiplin Kerja, Motivasi Kerja, dan Budaya Organisasi [Improving Teacher's Performance from the Factor of Work Discipline, Work Motivation, and Organizational Culture] - Virsa Sari Widuri (Jurnal Ketopong Pendidikan, 2022)
A school’s healthy organizational culture forms the foundation of culture which may become values among its members. School’s culture may trigger the improvement in work discipline and work motivation, which are ones of teachers’ performance evaluation criterions. The aim of this research is to find the effects of discipline, motivation, and organizational culture on teachers’ performance. It is important to conduct the research at School X in Tangerang Selatan as there has been noticed a phenomenon of teachers’ performance gap which caused hindrance in reaching school’s goals. The research was conducted at Sekolah X in Tangerang Selatan using census method and the Partial Least Square – Structural Equation Modelling (PLS-SEM) tool to analyze the results. The population of 42 people is the respondent or being censused. The findings concluded that the discipline, motivation, and organizational culture do have effect on the teachers’ performance, with the most influenced construct on teachers’ performance was the discipline. There were also found that the organizational culture effects the discipline and motivation among teachers of School X in Tangerang Selatan.